164k views
0 votes
-2(2x+3)=-4(x+1) - 2

1 Answer

4 votes

Answer:

All real numbers are solutions

Explanation:

Let's solve your equation step-by-step.

−2(2x+3)=−4(x+1)−2

Step 1: Simplify both sides of the equation.

−2(2x+3)=−4(x+1)−2

(−2)(2x)+(−2)(3)=(−4)(x)+(−4)(1)+−2(Distribute)

−4x+−6=−4x+−4+−2

−4x−6=(−4x)+(−4+−2)(Combine Like Terms)

−4x−6=−4x+−6

−4x−6=−4x−6

Step 2: Add 4x to both sides.

−4x−6+4x=−4x−6+4x

−6=−6

Step 3: Add 6 to both sides.

−6+6=−6+6

0=0

Answer:

All real numbers are solutions.

User Arbaz Alam
by
5.3k points